The super secret mystery - Barden, Stephanie (Barden, Stephanie. Cinderella Smith, 2013)
"A trip to the zoo has Cinderella Smith and her friends excited to start their endangered species reports--until all of the books on Cinderella's chosen animal go missing from the school library, leaving the Group in Cahoots to solve the mystery"--